Introducing vaccination against serogroup B meningococcal disease: An economic and mathematical modelling study of potential impact - Christensen, Hannah (Elsevier Science, 2013)
BACKGROUND: Meningococcal disease remains an important cause of morbidity and mortality worldwide. The first broadly effective vaccine against group B disease (which causes considerable meningococcal disease in Europe, the Americas and Australasia) was licensed in the EU in January 2013; our objective was to estimate the potential impact of introducing such a vaccine in England. METHODS: We developed two models to estimate the impact of introducing a new ‘MenB’ vaccine. The cohort model assumes the vaccine protects against disease only; the transmission dynamic model also allows the vaccine to protect against carriage (accounting for herd effects). We used these, and economic models, to estimate the case reduction and cost-effectiveness of a number of different vaccine strategies. RESULTS: We estimate 27% of meningococcal disease cases could be prevented over the lifetime of an English birth cohort by vaccinating infants at 2,3,4 and 12 months of age with a vaccine that prevents disease only; this strategy could be cost-effective at £9 per vaccine dose. Substantial reductions in disease (71%) can be produced after 10 years by routinely vaccinating infants in combination with a large-scale catch-up campaign, using a vaccine which protects against carriage as well as disease; this could be cost-effective at £17 per vaccine dose. CONCLUSIONS: New ‘MenB’ vaccines could substantially reduce disease in England and be cost-effective if competitively priced, particularly if the vaccines can prevent carriage as well as disease. These results are relevant to other countries, with a similar epidemiology to England, considering the introduction of a new ‘MenB’ vaccine.